Assessing the Financial Viability of Livestock Insurance in Karnataka - Pallavi, G. L.; Singh, Ajmer; Chandel, B. S.; Sendhil, R.; Lathwal, S. S.; Dhruva, V. C. (International Journal of Livestock Research, 2019)
To provide protection mechanism to the farmers and cattle rearers against any eventual loss of their animals due to death, Government of India (GOI) introduced the livestock insurance scheme during the years 2005-06. Under the scheme, high yielding cattle and buffaloes were insured at maximum of their current market price. Government incentivized farmers in terms of subsidy upto 50 per cent in the premium amount. Yet only 2 per cent of the milch animals in Karnataka state were insured till 2013-14. A sample of 120 farmers were collected from Bengaluru rural district of Karnataka. A simple random sampling technique was adopted to select sample at village level whereas state, district and taluks were selected purposively. The paper analyzed the aspect whether the livestock insurance was loss making proposition to the farmers or insurance companies or both. The study observed that the overall claim amount to premium amount collected ratio was found to be 0.93 and 0.89 for National Livestock Insurance Scheme in Karnataka and BAMUL group cattle insurance respectively, indicating the financial viability of livestock insurance in the study area.